Association between Fellowship Training, Surgical Volume, and Laparoscopic Suturing Techniques among Members of the American Association of Gynecologic Laparoscopists. (18th January 2016) - Mikhail, Emad; Scott, Lauren; Miladinovic, Branko; Imudia, Anthony N.; Hart, Stuart
Abstract : Study Objective . To compare surgical volume and techniques including laparoscopic suturing among members of the American Association of Gynecologic Laparoscopists (AAGL) according to fellowship training status. Design . A web-based survey was designed using Qualtrics and sent to AAGL members. Results . Minimally invasive gynecologic surgery (FMIGS) trained surgeons were more likely to perform more than 8 major conventional laparoscopic cases per month (63% versus 38%, P < 0.001, OR [95% CI] = 2.78 [1.54–5.06]) and were more likely to perform laparoscopic suturing during these cases (32% versus 16%, P < 0.004, OR [95% CI] = 2.44 [1.25–4.71]). The non-fellowship trained (NFT) surgeons in private practice were less likely to perform over 8 conventional laparoscopic cases (34% versus 51%, P = 0.03, OR [95% CI] = 0.50 [0.25–0.99]) and laparoscopic suturing during these cases (13% versus 27%, P = 0.01, OR [95% CI] = 0.39 [0.17–0.92]) compared to NFT surgeons in academic practice . Conclusion . The surgical volume and utilization of laparoscopic suturing of FMIGS trained surgeons are significantly increased compared to NFT surgeons. Academic practice setting had a positive impact on surgical volume of NFT surgeons but not on FMIGS trained surgeons.